Lithic technology studies in Colombia during the late Pleistocene and early Holocene (2015)
ABSTRACT: This paper provides an overview of the lithic technology of human groups that inhabited Colombian territory between the Late Pleistocene and the early Holocene. The chosen methodology was to document and compare the lithic technology regionally, in order to show the differences in theoretical and methodological approaches applied.